2023
DOI: 10.1177/13674935231171451
|View full text |Cite
|
Sign up to set email alerts
|

Working with children and young people in research: Supportive practices and pathways to impact

Abstract: Children and young people have much to contribute to the design and delivery of health research and care. Nevertheless, there are multiple barriers to meaningful and impactful involvement of children and young people. This narrative review synthesised existing literature on the involvement of children and young people as partners in health research. Authors screened electronic databases and reference lists to identify relevant studies. Data were extracted on how involvement was described, what young people con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The value of participatory research cannot be overstated. There is no current standardised description of its impact, but studies have identified common effects including improved research plans, learning among partners and academic researchers, and impact on policy makers ( 63 ). Increased relevance of research to patients, healthcare professionals and other end users is undeniable, avoiding research waste ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The value of participatory research cannot be overstated. There is no current standardised description of its impact, but studies have identified common effects including improved research plans, learning among partners and academic researchers, and impact on policy makers ( 63 ). Increased relevance of research to patients, healthcare professionals and other end users is undeniable, avoiding research waste ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…ice breakers. Visual aids were also used including a timetable at the start of the session, as recommended by findings from a recent review (Thomas et al, 2023). There were difficulties in meaningfully using visual schedules for every workshop as often the sessions changed depending on the children's needs and wishes.…”
Section: Reflections and Practical Guidancementioning
confidence: 99%